The National Historical Archive Library - Marías Martínez, Laura (Cuadernos de Historia Moderna, 2021)
The National Historical Archive Library belongs to the RBAE (Network of State Archive Libraries). It is a special library, both in terms of quantity and quality. On the one hand, it holds more than 30,000 volumes on history, archives and other related sciences, which are extremely useful for archivists and researchers. It also has some 300 titles of periodicals and an important collection of pamphlets. On the other hand, it stands out for its extraordinary rare and early printed books collection, most of which comes from the convent of Uclés. The Library’s modern collection is both a working instrument for archival work and a tool to support research, while the rare books[1] collection, apart from forming part of Spain’s bibliographic heritage, is of great interest to book historians. The aim of this paper is to outline a brief history of the Library